2014
DOI: 10.1371/journal.pone.0086154
|View full text |Cite
|
Sign up to set email alerts
|

N-Acetylgalactosamine Positive Perineuronal Nets in the Saccade-Related-Part of the Cerebellar Fastigial Nucleus Do Not Maintain Saccade Gain

Abstract: Perineuronal nets (PNNs) accumulate around neurons near the end of developmental critical periods. PNNs are structures of the extracellular matrix which surround synaptic contacts and contain chondroitin sulfate proteoglycans. Previous studies suggest that the chondroitin sulfate chains of PNNs inhibit synaptic plasticity and thereby help end critical periods. PNNs surround a high proportion of neurons in the cerebellar nuclei. These PNNs form during approximately the same time that movements achieve normal ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 49 publications
0
6
0
Order By: Relevance
“…Two pieces of evidence suggest that PNNs in the cerebellar nuclei serve a purpose other than inhibiting synaptic plasticity. (1) We recently showed that dissolving PNNs in the cerebellar nuclei had no impact on the strength or persistence of changes in saccade size elicited by long term saccade adaptation [ 72 ]. (2) As we show in Figure 10 , one of the ligands most likely to mediate inhibition of synaptic plasticity, PTP σ , is not expressed in the cerebellar nuclei in a manner consistent with this function.…”
Section: Discussionmentioning
confidence: 99%
“…Two pieces of evidence suggest that PNNs in the cerebellar nuclei serve a purpose other than inhibiting synaptic plasticity. (1) We recently showed that dissolving PNNs in the cerebellar nuclei had no impact on the strength or persistence of changes in saccade size elicited by long term saccade adaptation [ 72 ]. (2) As we show in Figure 10 , one of the ligands most likely to mediate inhibition of synaptic plasticity, PTP σ , is not expressed in the cerebellar nuclei in a manner consistent with this function.…”
Section: Discussionmentioning
confidence: 99%
“…Saccades are an ideal system for studying neural control of movement since they are well understood and can be measured precisely [ 33 , 57 ]. The feasibility of experimentally digesting chondroitin sulfate chains of PN with the enzyme chondroitinase ABC [ 58 ] has been shown in macaque fastigial nucleus [ 59 ]. Similar methods could be applied in the PPRF and RIMLF.…”
Section: Discussionmentioning
confidence: 99%
“…Second, it should be possible to selectively lesion PN in macaques and measure the effects on specific types of eye movements; the brainstem control of saccades would seem a good place to start, given the well‐established neural substrate for these eye movements. Such an approach has already been shown to be feasible through injecting the enzyme chondroitinase ABC to digest chondroitin sulfate chains of PN in the monkey fastigial nucleus neurons and performing saccade‐adaptation experiments . If an attempt to lesion PN surrounding PBN and OPN caused a saccadic palsy, then this might serve as a reductionist model to study the effects of lesioning PN in other areas of the brain and an accessible means to investigate the potential and mechanisms of action of putative therapies .…”
Section: Discussionmentioning
confidence: 99%